Mekanisme Titip Gadai Elektronik (HP) pada Titip Gadai Bursa Phone Pallangga, Gowa Sulawesi Selatan: Telaah Pemikiran Abu Hanifah - Putra, Andri Setia; Amir, Rahma (Universitas Islam Negeri Alauddin Makassar, 2023)
The main problem of this research is related to the Review of Islamic Law on the Process of Electronic Pawn Delivery (HP) Mechanism: Abu Hanifah's Thought Study (Bursha Phone Pallangga Pawn Tip Study, Gowa, South Sulawesi). The type of research carried out is field research that departs from observation and discovery of social facts that are studied using a statutory approach (statute approach). The results of this study show that the mechanism of pawning in Bursphone is the determination of the price of mortgaged goods determined by market prices, when there has been an agreement between the store owner and the customer will be given an agreement to return the money every one week gradually, and when customers who are due date and have not been able to redeem the mortgaged goods, The company will confirm to the customer and will give time with a period of 3 days. However, if the customer requests an extended ransom time, the store owner will still provide relief to the customer to extend the redemption time, but if the time requested by the customer still exceeds the given time limit, the customer's goods will become the sole property of the store owner. The pawn company Bursa Phone located in Pallangga, Gowa Regency, can be said to have met the requirements of pawnshops in Indonesia, because, in addition to paying attention to the benefits of the shop owner, it also does not forget to pay attention to the ability of customers related to the redemption of their goods by providing relief in the form of additional redemption time. Likewise, when viewed from the problems of Islamic law, this company has also fulfilled the requirements of Islamic law in carrying out its pawn mechanism, starting from the conditions, to the form of application carried out by shop owners, because in fact, pawn companies only want to ease the burden on the ummah by not ruling out the problem of agreements that have been made by the company.